PENGARUH UKURAN PERUSAHAAN, FREE ASSETS, ASSETS RETRENCHMENT, PERGANTIAN CEO, DAN LEVERAGE TERHADAP CORPORATE TURNAROUND (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2008-2013) - Nastiti, Prianka Ratri; Demi Pangestuti, Irene Rini (Faculty of Economics and Business Diponegoro University, 2016)
This research is an empirical study to analyze the factors that affect the company's financial performance improvement (corporate turnaround) at the manufacturing companies that are experiencing financial difficulties (financial distress) during the period 2008-2013. From 135 manufacturing companies listed in Indonesia Stock Exchange, designated 43 companies as samples by purposive sampling method. Tests in this study using logistic regression method. Factors tested in predicting the occurrence of turnaround are: the size of the company, free assets, assets retrenchment, CEO turnover, and leverage. By testing the feasibility of the model, it is stated that the model is fit for use in this study to allow for further testing. Statistical tests showed that the size of the companies and assets retrenchment significantly positive effect on corporate turnaround while variable leverage, free assets and the change of CEO does not affect thecorporate turnaround. The results of the study imply that the size of companies and assets retrenchment could increase the ability ofÂ corporate turnaround, butÂ not so with leverage, free assets and CEO turnover.